Breeding Drought-Tolerant Pearl Millet Using Conventional and Genomic Approaches: Achievements and Prospects - Srivastava, Rakesh K.; Yadav, O. P.; Kaliamoorthy, Sivasakthi; Gupta, S. K.; Serba, Desalegn D.; Choudhary, Sunita; Govindaraj, Mahalingam; Kholová, Jana; Murugesan, Tharanya; Satyavathi, C. Tara; Gumma, Murali Krishna; Singh, Ram B.; et al. (Frontiers in Plant Science, 2022)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is a C4 crop cultivated for its grain and stover in crop-livestock-based rainfed farming systems of tropics and sub-tropics in the Indian sub-continent and sub-Saharan Africa. The intensity of drought is predicted to further exacerbate climate change in growing regions, necessitating a greater focus on pearl millet breeding for drought tolerance. The nature of drought in the different target populations of pearl millet growing environments (TPE) is highly variable in its timing, intensity and duration. Pearl millet response to drought at various growth stages has been studied comprehensively. Dissection of drought tolerance physiology and phenology insights has helped in understanding the yield formation process under drought conditions. The overall understanding of TPE and differential sensitivity of various growth stages to water stress helped to identify target traits for manipulation through breeding in pearl millet for drought ecology. Recent advancement in high-throughput phenotyping platforms has made it realistic to screen large populations/germplasm for drought adaptive traits. The role of adapted germplasm has been emphasized for drought breeding as the measured performance under drought stress is largely an outcome of adaptation to stress environments. Hybridization of adapted landraces with selected elite genetic material has been testified to amalgamate adaptation and productivity. Substantial progress has been made towards the development of genomic resources that have been used to explore genomic variation, linkage mapping (QTLs), marker-trait association (MTA), and genomic selection (GS) in pearl millet. High-throughput genotyping (HTPG) platforms are now available at a low cost offering enormous opportunities in applying MAS in conventional breeding programs targeting drought tolerance. Next-generation sequencing (NGS) technology, micro-environmental modelling, and pearl millet whole genome re-sequence information covering circa 1,000 wild and cultivated accessions have helped to a greater understanding of germplasm, genomes, genes and markers. Their application in molecular breeding would lead to the development of high-yielding and drought-tolerant pearl millet cultivars. This review examines how the strategic use of genetic resources, modern genomics, molecular biology and shuttle breeding can further enhance the development and delivery of drought-tolerant cultivars.